The influence of Olympic triumph: exploring societal and political outcomes through sports stakeholder views - Zare, F.; Géczi, G. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
The purpose of this study was to qualitatively assess and describe the societal and political outcomes of elite sporting success from the stakeholders` perspective. In order to address the research questions and investigate a substantive issue, a grounded theory approach was employed. Using theoretical sampling, we identified participants who could contribute to the development of concepts or the filling of knowledge gaps. The theoretical sampling process involved four steps. The open-ended responses were analysed using NVivo software. A number of novel factors that can affect the political and societal outcomes of Olympic success have been identified in this study, including environmental issues, human rights, integration, accessibility, anti-discrimination, and anti-racism. This research has contributed to our understanding of the Olympic Games` success and can be used to inform future planning and decision-making.